Runoff‐mediated seasonal oscillation in the dynamics of dissolved organic matter in different branches of a large bifurcated estuary—The Changjiang Estuary. Issue 5 (7th May 2014) - Guo, Weidong; Yang, Liyang; Zhai, Weidong; Chen, Wenzhao; Osburn, Christopher L.; Huang, Xiao; Li, Yan
Abstract The Changjiang Estuary is a large bifurcated estuary where different hydrodynamic processes influence its South Branch compared to its North Branch. The South Branch is the dominant pathway of Changjiang River discharge, while the shallower and narrower North Branch is dominated by salt water intrusion, especially in the dry season. Absorption and fluorescence spectroscopy were measured along with dissolved organic carbon (DOC) concentrations to characterize the properties of dissolved organic matter (DOM) collected in different seasons during an extreme drought year in 2011. The refractory DOM from the Changjiang River flowed mainly through the South Branch, whereas in the lower South Branch, the input from the polluted Huangpu River contributed a large amount of biolabile DOM, demonstrating an anthropogenic perturbation from megacities. The DOM properties in the North Branch showed conservative behavior in the wet season, while noticeable addition was observed in the dry season, accompanied by the reversed flux of DOM from the North Branch to the South Branch, emphasizing the regular seasonal oscillation of the DOM dynamics in this monsoon‐controlled bifurcated estuary. The estuarine turbidity maximum zones played distinct roles on DOM dynamics in different estuarine environments. The DOC and chromophoric DOM (CDOM) abundance in the Changjiang River and other Chinese rivers were at lower levels compared to other world rivers, showing a characteristic of the regional CDOM‐poor features for many East Asia rivers.